Multidisciplinary Pain Management of Chronic Back Pain: Helpful Treatments from the Patients’ Perspective - Nees, Timo A.; Schiltenwolf, Marcus; Neubauer, Eva (Journal of Clinical Medicine, 2020)
Multidisciplinary pain management programs (MPMP) for patients suffering from chronic back pain include a variety of treatment modalities. The patients’ perceived helpfulness of these treatment modalities remains unclear. The aims of this prospective ...